Предмет:
МатематикаАвтор:
аноним(0,1 * x - 8)^2 + (0,1 * x + 8)^2 = 0,01 * х^2 - 0,8 * х - 0,8 * х + 64 + 0,01 * х^2 + 0,8 * х + 0,8 * х + 64 = 0,02 * х^2 + 128;
Подставим значение неизвестной х = -10 в упрощенное выражение:
0,02 * х^2 + 128 = 0,02 * (-10)^2 + 128 = 2 + 128 = 130;
Ответ: 130.
Автор:
augustokotoДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть